Spoof surface plasmon based planar antennas for the realization of Terahertz hotspots - Zhang, Yusheng (Sci Rep, 2015)
Novel spoof surface plasmon based terahertz (THz) antennas are realized using a few number of rectangular grooves perforated in ultrathin metal stripes and the properties of them, including both scattering cross sections and field enhancement, are numerically analyzed. The dependence of these properties on the incident angle and groove number is discussed and the results show that sharp resonances in scattering cross section spectra associated with strong local field enhancement can be achieved. These resonances are due to the formation of Fabry-Perot resonances of the spoof surface plasmon mode and it is found that the order of resonance exhibiting strongest field enhancements is found to coincide with the number of grooves at normal incidence, due to hybridization of the antenna resonance with the individual groove resonance. The terahertz hotspots within the grooves at resonances due to the local field enhancement may open up new possibilities for the investigation of terahertz-matter interactions and boost a variety of THz applications including novel sensing and THz detections. The planar stripe antennas with sharper resonances than dipolar-like resonances, together with their ease of fabrication may also promise new design methodology for metamaterials.